The economics of money and banking - Chandler V. Lester; Chandler, Lester Vernon (New York : Harper & Row, 1964)
This program examines government attempts to stabilize the economy, focusing on monetary policy. Concepts explored include fractional reserve banking, the deposits in chartered banks as a major component of the country's money supply, and how chartered bank reserves can be increased.
Includes bibliographical references and index.
aia 03/05/2018, rpm 07/05/2018
Loans
Keywords: Money; Banks and banking